A rapid review of early guidance to prevent and control COVID-19 in custodial settings - Lindsay A. Pearce; Alaina Vaisey; Claire Keen; Lucas Calais-Ferreira; James A. Foulds; Jesse T. Young; Louise Southalan; Rohan Borschmann; Ruth Gray; Sunita Stürup-Toft; Stuart A. Kinner (BMC, 2021)
Abstract Background With over 11 million people incarcerated globally, prevention and control of COVID-19 in custodial settings is a critical component of the public health response. Given the risk of rapid transmission in these settings, it is important to know what guidance existed for responding to COVID-19 in the early stages of the pandemic. We sought to identify, collate, and summarise guidance for the prevention and control of COVID-19 in custodial settings in the first six months of 2020. We conducted a systematic search of peer-reviewed and grey literature, and manually searched relevant websites to identify publications up to 30 June 2020 outlining recommendations to prevent and/or control COVID-19 in custodial settings. We inductively developed a coding framework and assessed recommendations using conventional content analysis. Results We identified 201 eligible publications containing 374 unique recommendations across 19 domains including: preparedness; physical environments; case identification, screening, and management; communication; external access and visitation; psychological and emotional support; recreation, legal, and health service adaptation; decarceration; release and community reintegration; workforce logistics; surveillance and information sharing; independent monitoring; compensatory measures; lifting control measures; evaluation; and key populations/settings. We identified few conflicting recommendations. Conclusions The breadth of recommendations identified in this review reflects the complexity of COVID-19 response in custodial settings. Despite the availability of comprehensive guidance early in the pandemic, important gaps remain in the implementation of recommended prevention and control measures globally, and in the availability of evidence assessing their effectiveness on reducing COVID-19 disease, impact on people in custody and staff, and implementation.